(3GdCQHY ebGdGJ dHWdjehSs - (3CHh RjO Mfjf Hf ESMGb GdYHGOis; (3Mfjf Hf GSMGb , CHh RjO Mfjf Hf GSMGb GdYHGOj,J (B260 (3g` s ((3HdOg bRhjf s)
(3ChdgG (B:s
(3ai UOQ GdcJGH(B: (3Ef GdCehQ GdJi jchf HgG JeGe JbOe GdeYQaI GdeCNhPI ef Yde GdfLhe jGShQi , CYXegG hCLdgG bOQkG EKfGf , CMOgeG , hgh GdebOe efgeG ai GdeQJHI hai GdbhI s
(3BNQgG (B:s
(3aEPG bO CJjfG Ydi Gdbhd ai CeQ GdehGdjO Ydi WQjbI GdLedI , aCQi Cfg ef GdhGLH Cf fNJe gPG GdcJGH ai gPG GdehVY JeJ GdebGdI GdQGHYI ef cJGH CQHY ebGdGJ s
(3ai CMcGe GdbVGA ef GdfLhe Ydi GdMhGOK hgh ai (B24 (3HGHkGs
(3HChdgG Jedc SfI (B1235(3g`s
(3HChdgG Jedc SfI (B1235(3g`s
(3HChdgG agQS ddehVhYGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3Gdadcs